Effects of post-acute COVID-19 syndrome on the functional brain networks of non-hospitalized individuals - Churchill, Nathan W.; Roudaia, Eugenie; Chen, J. Jean; Gilboa, Asaf; Sekuler, Allison; Ji, Xiang; Gao, Fuqiang; Lin, Zhongmin; Jegatheesan, Aravinthan; Masellis, Mario; Goubran, Maged; Rabin, Jennifer S.; et al. (Frontiers in Neurology, 2023)
Introduction The long-term impact of COVID-19 on brain function remains poorly understood, despite growing concern surrounding post-acute COVID-19 syndrome (PACS). The goal of this cross-sectional, observational study was to determine whether there are significant alterations in resting brain function among non-hospitalized individuals with PACS, compared to symptomatic individuals with non-COVID infection. Methods Data were collected for 51 individuals who tested positive for COVID-19 (mean age 41±12 yrs., 34 female) and 15 controls who had cold and flu-like symptoms but tested negative for COVID-19 (mean age 41±14 yrs., 9 female), with both groups assessed an average of 4-5 months after COVID testing. None of the participants had prior neurologic, psychiatric, or cardiovascular illness. Resting brain function was assessed via functional magnetic resonance imaging (fMRI), and self-reported symptoms were recorded. Results Individuals with COVID-19 had lower temporal and subcortical functional connectivity relative to controls. A greater number of ongoing post-COVID symptoms was also associated with altered functional connectivity between temporal, parietal, occipital and subcortical regions. Discussion These results provide preliminary evidence that patterns of functional connectivity distinguish PACS from non-COVID infection and correlate with the severity of clinical outcome, providing novel insights into this highly prevalent disorder.